Added Value of CHA2DS2-VASc Score to Safe Contrast Volume for Contrast Induced Nephropathy Prediction after Percutaneous Coronary Intervention - khalil, Wael Ali; Mohammad, Mohammad Gouda; Alshaer, Mohammad Hossam; Mageed, Mohammad Gamal Abd El (Jurnal Kardiologi Indonesia, 2023)
Background: The CHA2DS2-VASc score is utilized to order the danger of embolization in atrial fibrillation (AF). Also, it has been assessed the worse clinical scenario in acute coronary syndrome patients, regardless of having AF. The study aim was to use CHA2DS2-VASc score added to the safe contrast volume (Volume /CrCl) for contrast-induced nephropathy (CIN) early prediction post PCI. Patients and Methods: The study included two hundred fifty nine patients who underwent percutaneous coronary intervention . For each patient, The CHA2DS2-VASc score and Volume /CrCl were evaluated. The patients in our study were divided, according to CIN development into two groups. CIN was identified as a rise in serum creatinine >0.5 mg/dl or >25% increase in baseline within48 to 72 hours after PCI. Statistical analysis: the receiver operating characteristic analysis was used to detect the best cut off values to predict CIN, and we concluded the predictors of CIN through multivariate logistic regression analysis. Results: There was a positive correlation between Mehran score and CHA2DS2-VASc score. Independent predictors of CIN were Mehran score, Volume/CrCl ratio>3.2 and CHA2DS2-VASc >3, CHF or EF < 40%, hypotension, anemia, primary PCI and weight. If the patient had (CHA2DS2-VASc score>3 or Volume/CrCl >3.2), as a single predictor, we could predict CIN with (sensitivity 96.97 %, 95% CI 0.71 to 0.82). Conclusion: The CHA2DS2-VASc score and Volume/CrCl ratio are new predictor of CIN, and we can use the CHA2DS2-VASc score , safe contrast volume for early detection of CIN after PCI.This article has a related Erratum.